2012
DOI: 10.21831/jep.v1i2.665
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Profesionalisme Guru: Sebuah Harapan

Abstract: The teacher professionalism had to be improved because the teacher had the important roles to improve human resources quality. The several efforts can be done by the teacher is understanding the minimum standard of the profession, completing the teacher qualifications and competencies, creating the good partnership, improving the service-based working, and improving the creativity in use the very latest information and communication technologies. The improving of the teacher welfare supported the several effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 0 publications
0
20
0
21
Order By: Relevance
“…Based on the background of this study problem that teacher professsionalism is one of the benchmarks of the quality of education (Muhson, 2004). In addition, teacher competence has an important role in the teaching and learning process (Bustari, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the background of this study problem that teacher professsionalism is one of the benchmarks of the quality of education (Muhson, 2004). In addition, teacher competence has an important role in the teaching and learning process (Bustari, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This finding agrees with the study [18] in upgrading teacher's professionalism, the school facilitated development of various kinds of training programs, such as seminars, workshops, ugradings, and the like. Further, in increasing teacher's professionalism according to [19] such programs can be implemented through in-service training. Education and training programs are one effort to increase teacher's professionalism [20].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is contrary to the study Utami in [21], which found that Teacher's Commitment was directly and significantly affecting teacher's professionalism by contributing 22.40%. The result of anther study in [19][20][21] also found that the teacher's commitment affected positively and significantly on teacher's performances. It is, however, understood because the researchers did not place personal development and autonomy in the model under their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Peran Pendidik PAUD dalam melaksanakan pembelajaran pada Kelompok Bermain, Pos PAUD maupun bentuk pendidikan anak Usia Dini lainnya memang dituntut bertindak profesional, dalam artian bahwa peran pendidik PAUD sebagai pelaksana teknis fungsional dalam kegiatan pembelajaran mempunyai tugas untuk melaksanakan kegiatan pembelajaran pada pendidikan anak usia dini secara profesional sesuai dengan norma seorang pendidik. Hal ini sependapat dengan Muhson (2004) dan Tanang & Abu (2014) bahwa peran dan posisi strategis seorang guru adalah senantiasa meningkatkan kemampuan profesionalnya dalam menjalankan tugas dan kewajiban dalam meningkatkan kualitas sumber daya manusia. Peran sebagai pelaksana teknis di lapangan, maka peran pendidik PAUD yang profesional adalah pendidik yang mampu melaksanakan dan menciptakan program sesuai dengan potensi daerah, serta sesuai dengan kebutuhan masyarakat yang secara alamiah memiliki perbedaan-perbedaan dan keinginan.…”
Section: Pendahuluanunclassified